Retired para athletes hold limited leadership roles in Canadian national sport federations - Stevenson, C.; Mortenson, W. B.; Peng, T.-H.; Miniato, A.; Walker-Young, E.; Willsie, D.; Gruenig, S.; Bundon, A.; Lawson, S.; Landry, M.; Pollock, C. L. (Frontiers in Sports and Active Living, 2025)
Despite increasing support for Paralympic athletes in Canada, concerns have been raised about their limited involvement in leadership positions within the National Sport Federations (NSFs) that govern Paralympic sports in Canada. We sought to determine the representation of retired para athletes in leadership roles across Canadian NSFs, and identify strategies, facilitators and barriers to retaining para athlete expertise in these roles. An electronic survey was distributed via email to all 27 NSFs representing Canada's summer and winter Paralympic sports and total of 18 NSFs participated. Representation across all roles was found to be low, ranging from 5.29% in leadership positions, such as boards and committees, to 0.29% in classifier roles. Open-ended responses highlighted strategies for increasing para athlete inclusion in leadership roles after retirement from competition. Seven NSFs reported using formal and informal inclusion strategies. 10 NSFs relied solely on informal or reported no strategies. The most reported facilitator of inclusion was active recruitment, with ongoing communication between NSF leaders and retiring athletes. Conversely, the most reported barrier was the lack of representation of retired para athletes in leadership roles, which contributed to limited awareness of available opportunities. Currently, para sport in Canada is predominantly led and driven by non-disabled individuals, rather than the disabled individuals they purport to represent.